Upaya Peningkatan Hasil Belajar Dan Aktivitas Siswa Dalam Pembelajaran Fisika Melalui Model Guided Discovery Learning Dengan Metode Praktikum Kelas XI – IPA SMAN 106 Jakarta - Suripta Suripta (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2019)
This research is entitled “ effors to improve learning Outcomes and Student Activity on Physycs through Learning Model Discovery Learning Practicum Methode class XI-IPA SMAN 106 Jakarta. “ This research as a breakthrough in increasing creativity of learning management, base on the curriculum 2013. The prosess is directed to produce Indonesian people who are productive, creative, innovative, affective through strengthening integrated attiude, skills and knowledge. Thus the educators must improve the creativity of teaching methodes so that students are not bored and motivate student learning. Base on this discription, it is hope that the teacher is able to play role as on innovator through learning. This study uses a qualitative approach to optain data and analysis through reflective, participatory and collaborative studies. Program development is base on data and information from students, teachers and social setting naturally through twoncycles off classroom research, each of which is planning, implementing, observing and reflecting.To enhance the learning outcomes and student activities in learning physycs of action research, this class(CAR) presents Learning Guided Discovery learning Model Practicum Methode. This research was conducted at SMAN 106 Jakarta with two cycles. In the first cycle, some student are not familiar with the learning condition that use Learning Guided Discovery Learning Model Practicum Mthode. In the second cycle, progress has been seen in the learning process and student beging to creat learning condition that lead to learning approach of Learning Guided Discovery Learning Model Practicum Methode. From observations student activities increased from 45,14 % in the pre-cycle to 74,69% in cycle1 and 76,74 % in cycle 2. While the learning outcomes or daily assessment experienced an average increase of 66 in the pre-cycle assessment(before using the learning Guided Discovery Learning Model Practicum Methode) to 80,25 in the first cycle an average 84,06 in the 2 cycle. From this implemtation of Classroom Action Research(CAR), the first cycle, the second cycle can be concluded thad the Guided Discovery LearningModel Practicum Methode can improve learning outcomes and student activity in Physics learning at SMAN 106 Jakarta.